Games Used With Serious Purposes: A Systematic Review of Interventions in Patients With Cerebral Palsy - Lopes, Sílvia; Magalhães, Paula; Pereira, Armanda; Martins, Juliana; Magalhães, Carla; Chaleta, Elisa; Rosário, Pedro (Frontiers in Psychology, 2018)
The purpose of the present systematic review was to examine extant research regarding the role of games used seriously in interventions with individuals with Cerebral Palsy. Therefore, PubMed, PsyINFO, Web of Science, Scopus, and IEEE databases were used. Search terms included: “serious games” OR “online games” OR “video games” OR “videogame” OR “game based” OR “game” AND “intervention” AND “cerebral palsy”. After the full reading and quality assessment of the papers, 16 studies met the inclusion criteria. The majority of the studies reported high levels of compliance, motivation, and engagement with game-based interventions both at home and at the clinical setting intervention. Regarding the effectiveness of the use of games, the results of the studies show both positive and negative results regarding their effectiveness. The efficacy was reported to motor function (i.e., improvements in the arm function, hand coordination, functional mobility, balance and gait function, postural control, upper-limbs function) and physical activity. Findings of this review suggest that games are used as a complement to conventional therapies and not as a substitute. Practitioners often struggle to get their patients to complete the assigned homework tasks, as patients display low motivation to engage in prescribed exercises. Data of this review indicates the use of games as tools suited to promote patients’ engagement in the therapy and potentiate therapeutic gains.